Lecturers’ Attitudes and Readiness toward Teaching Students with Intellectual Disabilities in Higher Education Institutions in Nigeria - Atah, Cletus Akpo; Godwin Akeke, Mercy Nkiruka; Anthony, Godwin Bullem; Franca, Iroegbu Ngozi; Olom, Patricia Akwaya; Nsan, Nsan Njar; Chukwurah, Margaret Uchenna; Ushie, Godwin Beshibeshebe; Madukwe, Esther Chijioke; Bessong, Bessong Emmanuel; Undie, Joseph Bekeh; Udida, Fabian Ugbe; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Inclusive education plays a vital role in promoting equitable learning opportunities, particularly for students with intellectual disabilities in higher education institutions. The attitudes and readiness of lecturers to adopt inclusive teaching practices are crucial to the successful implementation of inclusive policies and pedagogies. Guided by the Theory of Planned Behaviour (TPB), this study investigates how lecturers’ attitudes, perceived social expectations, and perceived behavioural control influence their readiness to teach students with intellectual disabilities in Nigerian higher education institutions. Methods: The study adopted a descriptive survey design, involving 270 lecturers selected through accidental sampling from various higher education institutions across Nigeria. Data were collected using a structured questionnaire designed to assess lecturers' attitudes, institutional expectations, and perceived control over inclusive teaching practices. Descriptive statistics, such as the mean and standard deviation, were used to analyze the data, while independent t-tests were employed to test the hypotheses at a 0.05 level of significance. Results: The findings revealed that lecturers demonstrate a moderate to high level of readiness to implement inclusive teaching. Respondents reported willingness to participate in training, adopt inclusive strategies, and manage mixed-ability classrooms. Attitudes toward inclusion were largely positive. However, challenges were noted in areas such as adapting instructional materials and using assistive technologies, indicating limitations in perceived behavioural control. Conclusions: The study affirms the relevance of the Theory of Planned Behaviour in explaining lecturers' readiness for inclusive teaching. Addressing capacity gaps through targeted training and institutional support is essential for advancing inclusive education and achieving Sustainable Development Goal 4.